1996
DOI: 10.1093/genetics/142.3.865
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Dynein Function Is Essential in Drosophila melanogaster

Abstract: The microtubule motor cytoplasmic dynein has been implicated in a variety of intracellular transport processes. We previously identified and characterized the Drosophila gene Dhc64C, which encodes a cytoplasmic dynein heavy chain. To investigate the function of the cytoplasmic dynein motor, we initiated a mutational analysis of the Dhc64C dynein gene. A small deletion that removes the chromosomal region containing the heavy chain gene was used to isolate EMS-induced lethal mutations that define at least eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(31 citation statements)
references
References 31 publications
4
27
0
Order By: Relevance
“…For example, previous clonal analysis of the null allele robl l(2)k10408 (before cloning of the gene) showed reduced clone size but a normal frequency of clone generation (Roch et al, 1998). However, clonal analysis of a strong cytoplasmic dynein heavy chain allele found a complete absence of clones in most flies and only a few small clones in the wing and abdomen observed in some flies (Gepner et al, 1996). Together these experiments suggest that whereas the dynein heavy chain gene is required for cell viability, cells can accomplish all minimally required cell autonomous dynein roles in the absence of robl.…”
Section: Possible Roles Of the Robl/lc7 Family In Dynein Functionmentioning
confidence: 95%
“…For example, previous clonal analysis of the null allele robl l(2)k10408 (before cloning of the gene) showed reduced clone size but a normal frequency of clone generation (Roch et al, 1998). However, clonal analysis of a strong cytoplasmic dynein heavy chain allele found a complete absence of clones in most flies and only a few small clones in the wing and abdomen observed in some flies (Gepner et al, 1996). Together these experiments suggest that whereas the dynein heavy chain gene is required for cell viability, cells can accomplish all minimally required cell autonomous dynein roles in the absence of robl.…”
Section: Possible Roles Of the Robl/lc7 Family In Dynein Functionmentioning
confidence: 95%
“…Dynein, as assessed by immunostaining for the dynein heavy chain Dhc64C, accumulates into the early oocyte in a similar manner to osk mRNA (Li, McGrail, Serr, & Hays, 1994). In early egg chambers dynein forms part of a multiprotein complex that also contains Egalitarian (Egl), Bicaudal‐D (Bic‐D), and Lissencephaly‐1 (Lis‐1), and mutations affecting any dynein complex gene block oocyte differentiation (Gepner et al, 1996; Liu, Xie, & Steward, 1999; Mach & Lehmann, 1997; McGrail & Hays, 1997; Navarro, Puthalakath, Adams, Strasser, & Lehmann, 2004; Swan, Nguyen, & Suter, 1999). RNA injection experiments discussed in the preceding section examined both bcd and osk RNAs and suggested that this early stage of osk localization involves dynein‐directed transport (Clark et al, 2007).…”
Section: Localization and Translational Regulation Of Oskmentioning
confidence: 99%
“…Standard Drosophila genetics were performed at 25°C. The following stocks were used: apterous ME -NLS::dsRed (Richardson et al, 2007), ens swo (Metzger et al, 2012), Df-ens Δ3277 (Sung et al, 2008), khc 8 (Brendza et al, 1999), dhc [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] (Gepner et al, 1996), plp 5 (Martinez-Campos et al, 2004), Dmef2-Gal4 (Ranganayakulu et al, 1998), rP298-Gal4 (Menon and Chia, 2001), ubiquitin-Gal4[3xP3-GFP] (Baena-Lopez et al, 2013, UAS-Ens-HA (Metzger et al, 2012), UAS-2xEGFP (Halfon et al, 2002), UAS-EB1-YFP (Bulgakova et al, 2013), and patronin Δ2 (gift from M. Gonzalez-Gaitan, University of Geneva, Geneva, Switzerland). w 1118 (3605), yw (1495), UAS-Rab7.GFP (42706), UASp-GFP.Golgi (30902), UAS-GFP.KDEL (9899), Df(2L)BSC693 (26545), Df(3L) BSC441 ( 24945), hs-FLP, hs-SceI (25679), γ-tub23C A6-2 (5728), and γ-tub23C A14-9 (7041) were obtained from the Bloomington Drosophila Stock Center.…”
Section: Drosophila Geneticsmentioning
confidence: 99%